Physio-balneotherapy factors in the complex treatment of patients with gouty arthritis at the sanatorium stage of rehabilitation - Ананьєва, Тетяна (Slobozhanskyi Herald of Science and Sport, 2017)
Tеtіana Ananіeva Purpose: to analyze and summarize the main approaches to the appointment of the main physiotherapeutic and balneological factors in the complex treatment of patients with gouty arthritis in the conditions of sanatorium treatment. Material & Methods: analysis of modern scientific and scientific-methodological literature on the problem of physical rehabilitation of patients with gout. Results: the main approaches to the appointment of modern methods of physiotherapy in combination with hydropathic and mud factors in the complex treatment of patients with gouty arthritis at the sanatorium stage of rehabilitation. Conclusions: the results of the study can be used as a basis for compiling a comprehensive physical rehabilitation program for patients with gouty arthritis in a sanatorium stage of rehabilitation.